METHODS OF TEACHING INFORMATION TECHNOLOGY BASED ON MULTIMEDIA APPLICATIONS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article considers the issues of effective teaching of information technology with the help of multimedia applications. It analyzes modern pedagogical technologies, the use of digital resources in education, the role of multimedia media in the educational process, opportunities for strengthening the role of teachers and students. Opinions are given on teaching methods based on multimedia applications, tools for improving the effectiveness of the lesson. The study provides recommendations for teaching information technology science from an interactive approach.